Adaptation of Supply Chain Management for Community-Based Tourism: A Case Study of the Songkhla Lake Basin - Prommontree, Jutamas; Buranakul, Sorapol (Humanities and Social Sciences Journal of Pibulsongkram Rajabhat University, 2024)
The research pursued two primary objectives: firstly, to investigate the causal factors influencing the adaptation of supply chain management within the domain of community-based tourism, with a specific focus on its implications for enterprise sustainability, using the Songkhla Lake Basin as a case study; and secondly, to construct a tailored adaptation model for supply chain management in the context of this unique form of community-based tourism. This research conducted questionnaires and semi-structured interviews using specific random sampling methods, the study targeted a sample of 320 participants, including accommodation representatives, food vendors, and community tourism souvenir vendors. The statistical analysis for this research encompassed the use of percentages, means (averages), and standard deviations. Confirmatory Factor Analysis (CFA) was applied to analyze questionnaire data, while Logical Reasoning Analysis was utilized for the interpretation of interview data The findings indicate that, firstly, the structural equation model implying a harmonious alignment the empirical data under investigation. The following results: X2/df = 2.36, RMSEA = 0.07, NFI = 0.96, CFI = 0.98, and SRMR = 0.03. The outcomes of this analysis met the established criteria. This interpretation suggests that the factors within the structural equation model are suitable for explaining the adaptation of supply chain management in the context of community-based tourism. Secondly, the structural equations demonstrate that the most influential predictors of survival are external threats from multiple domains, including economic, environmental, social, cultural, and technological factors. The subsequent predictive factor, pertains to the supply chain adaptation within the domain of community-based tourism, which can be discerned through considerations of management, the service marketing mix, and community organizations factors. Furthermore, the research revealed that business survival is a result of the interplay of both primary factors, demonstrating a high reliability of 96 percent.